Comparison of different lining materials for field channels based on seepage characteristics - ANNIE S. S; Sukanya S; Er. Priya G. Nair (Guide) (Tavanur 2014 Kelappaji College of Agricultural Engineering and Technology)
Comparison of different lining materials for field channels based on seepage characteristics
Comparison of different lining materials for field channels based on seepage characteristics